Arctic soil carbon insulation averts large spring cooling from surface–atmosphere feedbacks - Rémi Gaillard; Philippe Peylin; Patricia Cadule; Vladislav Bastrikov; Frédérique Chéruy; Amélie Cuynet; Josefine Ghattas; Dan Zhu; Bertrand Guenet (Proceedings of the National Academy of Sciences, 2025)
The insulative properties of soil organic carbon (SOC) and surface organic layers (moss, lichens, litter) regulate surface–atmosphere energy exchanges in the Arctic through a coupling with soil temperatures. However, a physical description of this process is lacking in many climate models, potentially biasing their high-latitude climate predictions. Using a coupled surface–atmosphere model, we identified a strong feedback loop between soil insulation, surface air temperature, and snowfall. Without insulation, the latent heat needed for soil ice thawing leads to a late spring and summer cold bias in surface air temperature (above 2 °C) over Arctic regions. The integration of soil insulation eliminates this bias and significantly improves the simulation of permafrost dynamics. Our findings, including the potential consequences of large perturbations (e.g., fires), highlight the importance of combining soil water freezing with a physical representation of SOC and surface organic layer insulation in Earth system models, to improve Arctic climate predictions.